Reseñas de libros, por: Osvaldo Sunkel, Raimundo Barros, Julio Faúndez, Juan Valenzuela, Eduardo Ortíz, Enzo Faletto, Lucio Geller y Tomás Reichmann - Internacionales, Estudios (Estudios Internacionales, 1969)
-